Constructal design of an idealized arterial bypass graft subjected to Newtonian and non-Newtonian blood flow - Dutra, Rafael Fernando (Universidade do Vale do Rio dos Sinos, 2020)
Arterial bypass grafts tend to fail after some years due to Intimal Hyperplasia – an abnormal proliferation of smooth muscle cells that leads to restenosis and graft occlusion. In this regard and based on the Constructal Design method, this dissertation, that is presented in the form of two articles, seeks to investigate the effect of geometric parameters and the influence of Carreau rheological parameters on the flow through a bypass graft circumventing an idealized, partially-stenosed coronary artery. The computational model assumes steadystate fluid flow through an idealized model for a partially stenosed artery with a bypass graft. A Computational Fluid Dynamics model and a Response Surface Methodology were employed to assess the effects of bypass geometry on pressure drop. The first article presented the analysis for a Newtonian fluid. As the diameter ratio D1/D increased and the junction angle α decreased, the pressure drop decreased and so the dependence of pressure drop on the stenosis degree. The effects of diameter ratio were more pronounced than those of junction angle on the velocity field and wall shear stress. The optimum point for all cases was D1/D,opt equal to 1 and α,opt equal to 30°, which is corroborated by previous studies. In a second article, the differences in between the Newtonian and non-Newtonian results were presented, through the analysis of the influence of rheological parameters of the Carreau model for blood. All the response surfaces generated for both the Newtonian and non-Newtonian cases presented a great similarity. The results obtained demonstrated that non-Newtonian rheological parameters did not influence neither the shape of the response surfaces nor the optimum points found, although they have a great impact on pressure drop, mainly the parameters 𝜂∗ and n. Besides, it was also evaluated the effects on velocity and wall shear stress caused by the variation of rheological parameters, where, 𝜂∗ and n, appear to have a more pronounced influence than . Finally, the results found in this dissertation demonstrated that the application of the Constructal Design method in hemodynamics might be a good alternative to provide configurations with enhanced performance and to provide valuable results to the understanding of biological flows.
Keywords: Constructal design; Newtonian blood; Non-Newtonian blood; Carreau model; Coronary artery bypass graft; Dimensionless pressure drop; ACCNPQ::Engenharias::Engenharia Mecânica